CRANIOTOPOGRAPHIC CHARACTERISTICS OF RECTUS SINUS OF THE DURA MATER OF THE BRAIN IN PEOPLE OF MATURE AGE IN HEALTH - Serbin, S.I.; Dubyna, S.O.; Bondarenko, S.V.; Hryn, V.H.; Svintsytska, N.L.; Ustenko, R.L.; Bilash, V.P. (World of Medicine and Biology, 2024)
For our investigation, we collected cadaveric material from 40 people of different ages and gender. We have prepared corrosive preparations of the rectus sinus of the dura mater of the brain. Our research has a variety of research methods for morphological research: topographic-anatomical preparation on the macroscopic and microscopic levels, cranial-morphometric examination of the rectus sinus, hardening of acrylic plastic for the preparation of corrosive preparations for the rectus sinus of the dura mater of the brain, injection method. The mophometric indicators we collected from the rectus sinus were subject to variation-statistical analysis. We also use the method of computer-graphic analysis. The data from our research can be used in planning surgical interventions on the structures of the dura mater of the brain – first for everything on the rectus sinuses of the dura mater of the brain.
Keywords: human; mature age; dura mater of the brain; rectus sinus; craniotopographic method